2013
DOI: 10.1186/1479-5876-11-199
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived tissue slice grafts accurately depict response of high-risk primary prostate cancer to androgen deprivation therapy

Abstract: BackgroundEffective eradication of high-risk primary prostate cancer (HRPCa) could significantly decrease mortality from prostate cancer. However, the discovery of curative therapies for HRPCa is hampered by the lack of authentic preclinical models.MethodsWe improved upon tumorgraft models that have been shown to predict drug response in other cancer types by implanting thin, precision-cut slices of HRPCa under the renal capsule of immunodeficient mice. Tissue slice grafts (TSGs) from 6 cases of HRPCa were est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Adenocarcinoma also regressed after androgen deprivation in these PDXs. This finding is similar to previous studies, where castrate-tolerant cells have been identified in other cohorts of PDXs from moderate-to high-grade tumours [17,20,21]. The residual tumour cells in IDC-P and adenocarcinoma are not yet castrate-resistant, as they do not proliferate autonomously in the absence of systematic androgens.…”
Section: Discussionsupporting
confidence: 92%
“…Adenocarcinoma also regressed after androgen deprivation in these PDXs. This finding is similar to previous studies, where castrate-tolerant cells have been identified in other cohorts of PDXs from moderate-to high-grade tumours [17,20,21]. The residual tumour cells in IDC-P and adenocarcinoma are not yet castrate-resistant, as they do not proliferate autonomously in the absence of systematic androgens.…”
Section: Discussionsupporting
confidence: 92%
“…Organotypic cultures using 3D cultured tumor cells or live tissue slice have also been developed previously in evaluating clinical therapeutics (33-35). Most of tissue slice-based cultures and drug testing are in the format of 6-well or 24-well plate (36, 37), and tissue slice viability was measured with labor and time-intensive methods such as immunohistochemistry staining or western blotting, which are not applicable for large-scale drug testing (19, 27). In our system, the LTSA can be performed in a 96-well-plate format and allows testing drug sensitivity in 3-5 days objectively with a commercially available reagent, which will significantly reduce the time and resources compared to the test in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…10 weeks), and well within the time frame required to modulate proliferation in PDX models. For example, changes in proliferation can be detected within 3 days after castration and 4 weeks after testosterone administration [28, 29], or after 1 week of other androgen-targeted agents, such as Enzalutamide (Taylor, unpublished data).…”
Section: Discussionmentioning
confidence: 99%